2017
DOI: 10.5541/eoguijt.336651
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Order Generalized Thermoelastic Problem in a Thick Circular Plate with Periodically Varying Heat Source

Abstract: This paper is concerned with fractional order thermoelastic response due to a heat source whose magnitude varies periodically with time within the context of generalized thermoelasticity with one relaxation time. Traction free boundary conditions are considered and the thick circular plate is subjected to a given axisymmetric temperature distribution. Integral transform technique is used to derive the solution in the transformed domain. Laplace transforms are inverted using a numerical scheme. Mathematical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The key that was derived by Deshmukh et al [41] for an isotropic, homogeneous, elastic hollow is compatible with the present thermoelastic solutions that were determined. In this piece of research, a fractional-order constitutive model and the classic continuity equation are brought together.…”
Section: Deduction and Validation Of The Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The key that was derived by Deshmukh et al [41] for an isotropic, homogeneous, elastic hollow is compatible with the present thermoelastic solutions that were determined. In this piece of research, a fractional-order constitutive model and the classic continuity equation are brought together.…”
Section: Deduction and Validation Of The Resultssupporting
confidence: 88%
“…(ii) Taking 0   in Eq. ( 5), the equation reduces to the classical Fourier heat conduction model [41] as given in Eq. ( 51) with a solution in Eq.…”
Section: Deduction and Validation Of The Resultsmentioning
confidence: 99%
“…Authors have confirmed that very little work has been reported in this field due to the complicated nature of the generalized form of the mathematical equation. Tripathi et al [48] investigated an issue by subjecting a circular plate to the research of axisymmetric temperature distribution. This was accomplished by applying traction-free boundary conditions and periodically varying the heat source that was considered to acquire the desired results.…”
Section: The Behaviour Of Thermoelasticity In a Circular Platementioning
confidence: 99%
“…Youssef and Abbas (2014) considered fractional order thermal conductivity as a linear function of temperature in the perspective of fractional order generalized thermoelasticity. Tripathi, Deshmukh, and Verma (2017) studied the generalized thermoelasticity fractional order thermoelastic response due to a heat source that varies periodically with time with one relaxation time. Abbas (2018) studied the effect of fractional order 2-D GN-III model due to thermal shock for weak, normal and strong conductivity.…”
Section: Introductionmentioning
confidence: 99%